2022
DOI: 10.1007/s40120-022-00395-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Syndrome is Rarely Associated with Damage of the Nervous System: Findings from a Prospective Observational Cohort Study in 171 Patients

Abstract: Introduction The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can affect multiple organs. Reports of persistent or newly emergent symptoms, including those related to the nervous system, have increased over the course of the pandemic, leading to the introduction of post-COVID-19 syndrome. However, this novel syndrome is still ill-defined and structured objectification of complaints is scarce. Therefore, we performed a prospective observational cohort study to better define and vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 69 publications
7
22
0
9
Order By: Relevance
“…Brain stem dysfunction [36], a reduced cerebral blood flow [31,82] and the involvement of the ANS [25,26,30,31,[37][38][39] are discussed with respect to long COVID. Recently, preinfection psychological distress was discussed as risk factor for long COVID, too [75,83]. This is in line with the self-reported stress prior to acute infection regarding the patients of the present study.…”
Section: Neurophysiological Considerations With Respect To the Reacti...supporting
confidence: 88%
“…Brain stem dysfunction [36], a reduced cerebral blood flow [31,82] and the involvement of the ANS [25,26,30,31,[37][38][39] are discussed with respect to long COVID. Recently, preinfection psychological distress was discussed as risk factor for long COVID, too [75,83]. This is in line with the self-reported stress prior to acute infection regarding the patients of the present study.…”
Section: Neurophysiological Considerations With Respect To the Reacti...supporting
confidence: 88%
“…Moreover, despite several studies detecting changes in brain microstructure of people with post-COVID-19 with structural MRI (Colonna et al 2020 ; Freeman et al 2021 ; Hixon et al 2021 ; Nuzzo et al 2021 ; Cecchini et al 2022 ) and DTI (Liu et al 2019 ; Tian et al 2020 ; Qin et al 2021 ), no correlations with fatigue symptoms have been reported. Other recent studies found that post-COVID-19 symptoms were rarely associated with damage of the central or peripheral nervous system (Fleischer et al 2022 ) or alterations in regional cerebral glucose metabolism (Dressing et al 2022 ). Moreover, the Fleischer and colleagues concluded that psychosomatic mechanisms, such as somato-sensoric amplification may play a role in the pathogenesis of post-COVID-19 symptoms (Fleischer et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies found that post-COVID-19 symptoms were rarely associated with damage of the central or peripheral nervous system (Fleischer et al 2022 ) or alterations in regional cerebral glucose metabolism (Dressing et al 2022 ). Moreover, the Fleischer and colleagues concluded that psychosomatic mechanisms, such as somato-sensoric amplification may play a role in the pathogenesis of post-COVID-19 symptoms (Fleischer et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations